CORRELATION BETWEEN AGE AND PARITY WITH THE RESULT OF VISUAL INSPECTION WITH ACETIC ACID (VIA) IN PEKALONGAN REGENCY - Lia Dwi Prafitri; S Suparni; Nur Izzah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
Cancer is one of the leading causes of death worldwide. The high prevalence of cancer in Indonesia needs to be monitored by preventing and early detection measures that health service providers have taken. Cervical cancer screening is carried out by Visual Inspection with Acetic Acid (VIA). This study aimed to determine the relationship between women's age, parity, and pregnancy 35 years with the results of the VIA examination. This research was an observational analytic study with a cross-sectional approach. The sample of this study was the total population who followed the VIA examination in Pekalongan Regency in 2018 and obtained 216 respondents. Multivariate analysis in this study was using multiple logistic regression. The results of this study indicate that there is no significant relationship between age and pregnancy 35 years old with VIA examination results (p-value:0.217 and 0.624). There is a significant relationship between parity and the results of the VIA examination (p-value:0.015). For health workers, especially midwives, should motivate married women and risk experiencing cervical cancer to carry out VIA examinations regularly. The Public Health Office should provide the facilities and infrastructure in all health facilities so that the public can carry out VIA examinations regularly, periodically in their respective territories. Keywords: Age, Parity, VIA